Pricing Strategies and Their Impact on Consumer Buying Behavior: An Empirical Study of Kathmandu’s Organized FMCG Retail Market - Khanal, Meg Nath (Journal of Interdisciplinary Studies, 2025)
This study aims to determine the impact of pricing strategies on consumer buying behavior on FMCG products inside Kathmandu valley. The causal and descriptive research design was employed in the study to investigate the cause-and-effect relationship between pricing strategies and consumer buying behavior on FMCG products inside Kathmandu Valley. Data was gathered from 250 respondents through structured questionnaire distributed via Google forms and convenience sampling was used. Quantitative analysis involved both descriptive and inferential statistics, employing the SPSS. Out of the five pricing strategies considered for the study, discount, psychological, competitive and penetration pricing had a positive and significant impact on consumer buying behavior. However, bundle pricing didn’t have a positive significant impact on consumer buying behavior. This study contributes valuable insight to retails determining correct pricing strategy for different products. The application of this study is extensive. Industry, professional, researchers and policymakers by advancing understanding and best practices in FMCG and retail industries, collectively fostering a more responsible offering.